1980
DOI: 10.1001/archpedi.1980.02130130038012
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Zinc Metabolism During the Course of the Nephrotic Syndrome

Abstract: \s=b\The plasma zinc concentration and quantitative urinary zinc excretion were studied in 105 pediatric patients with the nephrotic syndrome or nephritis-nephrosis. The plasma level was decreased to a mean value of 51.7 \g=m\g/dLin patients with the nephrotic syndrome (controls, 85 \ g=m\ g/ dL). The rate of urinary zinc excretion was not different from that of the controls, with the exception of patients whose disease was in the polyuric phase of beginning remission where it was fivefold higher and those who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 12 publications
1
18
1
Order By: Relevance
“…We found that plasma selenium levels were low in NS patients during both active and remission phase and plasma selenium level had a tendency to return to normal in remission, this is in good agreement with the results of selenium published by Mishra et al [9]. Additionally, we found that plasma zinc level was lower in the NS group in active and remission phase, which is in good agreement with the results published by Reimold [16] and Perrone et al [7], but not with those of Mishra et al [9], who observed no difference between NS and control groups in terms of plasma zinc level. Furthermore, in an experimental study, low serum v and high urinary zinc excretion were observed in nephrotic rats [17].…”
Section: Discussionsupporting
confidence: 92%
“…We found that plasma selenium levels were low in NS patients during both active and remission phase and plasma selenium level had a tendency to return to normal in remission, this is in good agreement with the results of selenium published by Mishra et al [9]. Additionally, we found that plasma zinc level was lower in the NS group in active and remission phase, which is in good agreement with the results published by Reimold [16] and Perrone et al [7], but not with those of Mishra et al [9], who observed no difference between NS and control groups in terms of plasma zinc level. Furthermore, in an experimental study, low serum v and high urinary zinc excretion were observed in nephrotic rats [17].…”
Section: Discussionsupporting
confidence: 92%
“…In this work, the levels of Zn decreased slightly in the spleen and lungs (81 and 87% of the control values, respectively) and were normal in 5 other tissues, therefore, these rats are not typically Zn deficient as those produced by ingestion of a Zn-deficient diet [23]. In con trast, in humans with NS, low Zn levels in hair [2,4], erythrocytes [4] and leukocytes [4] have been observed. The mechanism(s) involved in the metabolic alterations of Cu and Zn in PAN-nephrotic rats remain(s) unknown.…”
Section: Discussionmentioning
confidence: 58%
“…Patients with nephrotic syndrome (NS) have low serum levels of zinc (Zn) [1][2][3][4][5][6]. In addition, low levels of Zn in leukocytes [4], hair [2,4] and erythrocytes [4] have also been found in these patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations